La reconstruction de l’architecture ottomane par les sociétés locales : le cas des monuments ottomans de Giannitsa, Grèce - Paschalis Androudis; Maria Triantafyllidou (Cahiers Balkaniques)
Abstract: for a long time, the Ottoman architecture in Greece – as in the Balkans, synonymous with the Ottoman occupation, was neglected or even destroyed; the wars having completed the destruction, only the "reusable" buildings survived. This article shows, with the example of Giannitsa, that mentalities gradually changed and that at the end of the 20th century, not only archaeologists, but also local societies and the municipality, showed interest in this past. This was the case for the monument of Gazi Evrenos, the Iskender Bey mosque and the Clock Tower.